Morphological characterization in the genus Passiflora L.: an approach to understanding its complex variability - Ocampo Pérez, John A.; D'Eeckenbrugge, Geo Coppens (Springer, 2017)
Morphological variation was studied in 124 accessions from 61 Passiflora L. species. Twenty-four quantitative descriptors selected for their high variation among subgenera were submitted to a principal component analysis. The first principal component (32% of total variance) was associated with flower length and secondarily with floral cup constriction, the second (27%) with flower width and bract shape, and the third (14%) with peduncle branching, stem width, and leaf length, which relates it to the differentiation of subgenera Astrophea and Deidamioides. The projection of accessions in the resulting tridimensional space consistently separates the four subgenera, as well as supersection Tacsonia of subgenus Passiflora. A neighbor joining analysis, on a selection of 32 qualitative traits and four categorized quantitative variables, clustered species according to their chromosome number and, within subgenus Passiflora, separated supersections Tacsonia (pollinated by the sword-billed hummingbird) and Distephana (pollinated by shorter-billed hummingbirds) from all other, bee-pollinated, species. Thus, the morphological study allows separating the effects of genome evolution from those of more recent and independent coevolutions concerning the pollination syndromes of supersections Tacsonia and Distephana. Within subgenus Decaloba, diverging subclusters are consistent with supersections and particular sections, with the partial exception of supersection Decaloba. Within supersection Tacsonia, subclusters correspond to one or two sections, pointing to overclassification in the current taxonomy. Among the bee-pollinated species of subgenus Passiflora, only supersection Laurifolia is clearly validated. Most of these results are consistent with molecular phylogenetic studies, except for interspecific relations among bee-pollinated species of subgenus Passiflora, which appear particularly difficult to classify.